ESTRUCTURA TRIDIMENSIONAL DE LA CITOQUININA N-BENZIL 9 (2 TETRAHIDROPIRANYL) ADENINE UTILIZANDO EL MÉTODO DE RESONANCIA MAGNÉTICA NUCLEAR - Huertas, Angélica; Departamento de Física Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2004)
In order to understand the biological function of the molecules that form living beings, it is necessary to know their three-dimensional structure, because this verifies that the function depends more on the space distribution that on its components. The objective of the present work is to determine the fitohormona  structure. One of the methods that exists  to determine these structures is the magnetic resonance nuclear  pulsation which was chosen for this work. This method differs from the  resonance of continuous wave in the fact that the variable magnetic field  is applied in form of pulses and its amplitude cannot be considered like a perturbation to the system. The determination of the structure requires the taking the unidimensionales spectra of H1, C13 and the   Distortionless Enhacement by Polarization Transfer (DEPT); the last one is a sequence of pulses that allows to differentiate between carbons with three, two and one hydrogen. With the aid of the C13 spectrum it is also possible distinguish the carbons that are not connected with any   hydrogen. In addition to these, the following bidimensional spectra were necessary: 1) Heteronuclear Multiple Quantum Correlation (HMQC)  which correlates hydrogens with carbons that are connected; 2) Heteronuclear Multiple Bond Correlation (HMBC) that correlates carbons with hydrogen’s that have two or three links; 3) Correlation   Spectroscopy (COSY) which shows the correlation between hydrogen’s that have two or three links; and 4) Nuclear Overhauser Effect  Spectroscopy (NOESY) which correlates hydrogen’s that are distant  from each other less than 5 Å. From the data obtained from the analysis of these spectra the model of fitohormona, which resulted from the work, was deduced.